PlMYB308 Regulates Flower Senescence by Modulating Ethylene Biosynthesis in Herbaceous Peony - Ji, Xiaotong; Wang, Meiling; Xu, Zhuangzhuang; Wang, Kai; Sun, Daoyang; Niu, Lixin (Frontiers in Plant Science, 2022)
Herbaceous peony is an important cut-flower plant cultivated worldwide, but its short vase life substantially restricts its economic value. It is well established that endogenous hormones regulate the senescence process, but their molecular mechanism in flower senescence remains unclear. Here, we isolated a MYB transcription factor gene, PlMYB308, from herbaceous peony ﬂowers, based on transcriptome data. Quantitative real-time PCR analysis showed that PlMYB308 is strongly up-regulated in senescing petals, and its expression was induced by abscisic acid or ethylene and reduced by gibberellin in petals. Treatment with abscisic acid or ethylene accelerated herbaceous peony petal senescence, and gibberellin delayed the process. PlMYB308 silencing delayed peony flower senescence and dramatically increased gibberellin, but reduced ethylene and abscisic acid levels in petals. PlMYB308 ectopic overexpression in tobacco accelerated flower senescence and reduced gibberellin, but increased ethylene and abscisic acid accumulation. Correspondingly, 5 endogenous hormone biosynthetic genes showed variable expression levels in petals after PlMYB308 silencing or overexpression. A dual-luciferase assay and yeast one-hybrid analysis showed that PlMYB308 specifically binds the PlACO1 promoter. Moreover, treatment with ethylene and 1-MCP can accelerate PlMYB308 silencing-reduced senescence and delay PlMYB308- overexpression-induced senescence. We also found that PlACO1 silencing delayed senescence in herbaceous peony petals. Taken together, our results suggest that the PlMYB308-PlACO1 regulatory checkpoints positively mediate the production of ethylene, and thus contribute to senescence in herbaceous peony flowers.